2013
DOI: 10.3899/jrheum.121029
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Spondyloarthropathy in Patients with Ulcerative Colitis: A Population-based Study

Abstract: Objective Spondyloarthritis (SpA) is an important extraintestinal manifestation of inflammatory bowel disease (IBD). We aimed to assess the cumulative incidence and clinical spectrum of SpA in a population-based cohort of patients with ulcerative colitis (UC). Methods The medical records of a population-based cohort of Olmsted County, Minnesota residents diagnosed with UC from 1970 through 2004 were reviewed. Patients were followed longitudinally until moving from Olmsted County, death, or June 30, 2011. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…Incidence and prevalence of SpA has been reviewed recently, but there are very few data available on the prevalence of IBD‐related SpA and to our knowledge, none on SpA manifestations of IBD patients on TNF inhibitors. One recent study with a cohort including 365 ulcerative colitis patients, of whom 40 developed spondyloarthropathy, found that the cumulative prevalence of all forms of SpA increased from 4.8% at 10 years to 13.7% at 20 years and 22% at 30 years after the diagnosis of ulcerative colitis . This value was slightly greater than what had previously been described in a patient‐based cohort of Crohn disease diagnosed over the same time period …”
Section: Discussionmentioning
confidence: 73%
“…Incidence and prevalence of SpA has been reviewed recently, but there are very few data available on the prevalence of IBD‐related SpA and to our knowledge, none on SpA manifestations of IBD patients on TNF inhibitors. One recent study with a cohort including 365 ulcerative colitis patients, of whom 40 developed spondyloarthropathy, found that the cumulative prevalence of all forms of SpA increased from 4.8% at 10 years to 13.7% at 20 years and 22% at 30 years after the diagnosis of ulcerative colitis . This value was slightly greater than what had previously been described in a patient‐based cohort of Crohn disease diagnosed over the same time period …”
Section: Discussionmentioning
confidence: 73%
“…9 Nevertheless, the prevalence of spondyloarthritis in IBD is reported from several cohorts outside the USA, 10 – 14 and one study from Olmsted County, Minnesota, estimated that the cumulative incidence of spondyloarthritis among patients with IBD after 10 years was 6.7% [95% confidence interval (CI) 2.5%–6.7%]. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Spondyloarthropathy is divisible in humans to five varieties [1,2,66]. One is associated with the skin disease, psoriasis.…”
Section: Discussionmentioning
confidence: 99%